A Cellular Automata-Based Simulation Tool for Real Fire Accident Prevention. (14th February 2018) - Czerniak, Jacek M.; Zarzycki, Hubert; Apiecionek, Łukasz; Palczewski, Wiesław; Kardasz, Piotr
Abstract : Many serious real-life problems could be simulated using cellular automata theory. There were a lot of fires in public places which kill many people. Proposed method, called Cellular Automata Evaluation (CAEva in short), is using cellular automata theory and could be used for checking buildings conditions for fire accident. The tests performed on real accident showed that an appropriately configured program allows obtaining a realistic simulation of human evacuation. The authors analyze some real accidents and proved that CAEva method appears as a very promising solution, especially in the cases of building renovations or temporary unavailability of escape routes.